Remote Sensing Of Archaeology (Damascus University Journal of arts and humanities sciences, 2021)
Remote sensing is one of the modern sciences, which managed in a short period to play an important role in various areas, such as agriculture and geology, and other sciences; it has also played an important role due to the development it brought to the field of archaeological research and documentation.  This search deals with in its first part with the definition of remote sensing and the most important historical defining moments of the origin of this science. It also introduces the main stages of the development and methodology of this science, and its main available tools and devices. The research analyzes also the most important remote sensing application in some other sciences.  The second part deals with the connection of remote sensing and its application in the field of archaeology, along with the most important techniques used in the archaeological search.  Finally, this search deals with the remote sensing application in the field of the archaeological GIS, and its role in the protection and maintenance of archaeological sites.
Keywords: Remote Sensing Of Archaeology